PENGARUH MOTIVASI DIRI DAN PEMBERDAYAAN DOWN LINE TERHADAP EFEKTIVITAS KEPEMIMPINAN TRANSFORMASIONAL PADA PT. RATU NUSANTARA DI KOTA AMBON - Juliana Latuihamahina; Harvey Hiariey (Fakultas Ekonomi dan Bisnis Universitas Pattimura, 2020)
This study aims to analyze the influence of self-motivation and empowerment of human resources (down line) on the effectiveness of transformational leadership (study at PT.Ratu Nusantara in Ambon City), using the several technical analysis model / tool. There are several techniques / approaches to collecting data, namely through interviews, observations, questionnaires and literature. Indicators used to measure the effect of self motivation and downline empowerment on the effectiveness of transformational leadership are motivation, namely the need for achievement, affiliation needs, power needs. Whereas for empowerment that builds strengths and resources by encouraging, motivating and raising employee awareness of their authority and striving for their development. While the effectiveness of transformational leadership is a leader with integrity according to words and actions, which shows the attitude of trustworthiness / honesty as the foundation of a trusting relationship between leaders and employees. The results showed that the coefficient of determination was 0.563 or 56.3%. This means that the two independent variables (self-motivation variables and empowerment variables) in this study were only able to explain 56.3% of the variation that occurred in the dependent variable (the effectiveness of transformational leadership). While other variations of 100% - 56.3% = 43.7% are explained by other variables not explained in this research model. Keyword: Self Motivation, Empowerment of Human Resources (down line), Transformational Leadership